A clinical follow-up of 35 Brazilian patients with Prader-Willi Syndrome (Clinics, 2012)
OBJECTIVE: Prader-Willi Syndrome is a common etiology of syndromic obesity that is typically caused by either a paternal microdeletion of a region in chromosome 15 (microdeletions) or a maternal uniparental disomy of this chromosome. The purpose of this study was to describe the most significant clinical features of 35 Brazilian patients with molecularly confirmed Prader-Willi syndrome and to determine the effects of growth hormone treatment on clinical outcomes. METHODS: A retrospective study was performed based on the medical records of a cohort of 35 patients diagnosed with Prader-Willi syndrome. The main clinical characteristics were compared between the group of patients presenting with microdeletions and the group presenting with maternal uniparental disomy of chromosome 15. Curves for height/length, weight and body mass index were constructed and compared between Prader-Willi syndrome patients treated with and without growth hormone to determine how growth hormone treatment affected body composition. The curves for these patient groups were also compared with curves for the normal population. RESULTS: No significant differences were identified between patients with microdeletions and patients with maternal uniparental disomy for any of the clinical parameters measured. Growth hormone treatment considerably improved the control of weight gain and body mass index for female patients but had no effect on either parameter in male patients. Growth hormone treatment did not affect height/length in either gender. CONCLUSION: The prevalence rates of several clinical features in this study are in agreement with the rates reported in the literature. Additionally, we found modest benefits of growth hormone treatment but failed to demonstrate differences between patients with microdeletions and those with maternal uniparental disomy. The control of weight gain in patients with Prader-Willi syndrome is complex and does not depend exclusively on growth hormone treatment.